2017
DOI: 10.3762/bjnano.8.121
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic characterization and thermogravimetric analysis of two series of substituted (metallo)tetraphenylporphyrins

Abstract: Subsequent treatment of H2TPP(CO2H)4 (tetra(p-carboxylic acid phenyl)porphyrin, 1) with an excess of oxalyl chloride and HNR2 afforded H2TPP(C(O)NR2)4 (R = Me, 2; iPr, 3) with yields exceeding 80%. The porphyrins 2 and 3 could be converted to the corresponding metalloporphyrins MTPP(C(O)NR2)4 (R = Me/iPr for M = Zn (2a, 3a); Cu (2b, 3b); Ni (2c, 3c); Co (2d, 3d)) by the addition of 3 equiv of anhydrous MCl2 (M = Zn, Cu, Ni, Co) to dimethylformamide solutions of 2 and 3 at elevated temperatures. Metalloporphyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is both challenging and motivating to investigate how to separate the 2D nano-ribbons from surfaces and to build multilayer devices from them. Thus, the results presented here gave plenty of stimuli to continue our joint efforts [ 60 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is both challenging and motivating to investigate how to separate the 2D nano-ribbons from surfaces and to build multilayer devices from them. Thus, the results presented here gave plenty of stimuli to continue our joint efforts [ 60 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that such studies would allow one to find suitable (metallo)porphyrins to explore interesting fields such as spintronic applications by coupling for example ferromagnetic substrates with suitable porphyrin structures. Consequently, we started to synthesize two new series of (metallo)porphyrins for related studies in which the metal centers and the terminal groups were varied [ 60 ]. Unfortunately, all of these (metallo)porphyrins were not suited for OMDB as they all thermally decomposed before sublimation (see below).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, instead of four bands, two (1 and 2) bands are observed, with noticeably different intensities. It should be noted that the form of the electronic absorption spectra of porphyrins noticeably differs for different porphyrins and in different media [19][20][21].…”
Section: Chemistrymentioning
confidence: 99%
“…In this Thematic Series we summarize selected examples of the collaborative work in which at least two groups were involved. The range of considered molecules spans from heterotrinuclear bis(oxamato)-type and bis(oxamidato)-type complexes [ 1 3 ], to exchange-coupled dinickel complexes [ 4 ], metallo-phthalocyanines [ 5 7 ], metallo-porphyrins [ 8 9 ] and charge-transfer complexes [ 10 11 ], to metal-free molecules like pentacene-derivatives [ 12 ], fullerenes [ 13 ], trimesic acid [ 14 ], or organic ferromagnets [ 15 ]. Besides the internal cooperation, the Research Unit greatly profited from excellent talks and thorough discussions with external guests joining our scientific workshops and we are happy to host six articles from our invited guests with topics beyond the molecular systems investigated in our Research Unit, for example: theoretical predictions on metal/C 60 interfaces [ 16 ], magneto-resistive donor/acceptor transistors [ 17 ], spin-crossover complexes [ 18 ], ferromagnetic thin films obtained from organic blends [ 19 ], and theoretical calculations on 2D porphyrin-based networks for spintronics [ 20 ].…”
mentioning
confidence: 99%